Irregularising Human Mobility : EU Migration Policies and the European Commission's Role - Carrera, Sergio; Colombi, Davide (SpringerBriefs in law., 2024)
What is the history and current state of play of EU law and policy covering irregularised human mobility? What has been the role and contributions of the 2019-2024 European Commission as regards EU migration policy? Through the concept of irregularity assemblages, this book investigates how migration policies have been problematised at the EU institutional level, in particular by the European Commission. It critically assesses the assumptions lying behind the Commission's political priorities, agendas and policy outputs.The overriding priority driving EU migration policy has been the expulsion, policing and criminalisation of people framed or categorised as 'irregular migrants'. The analysis shows how Commission has failed to effectively perform its role as guardian of the Treaties and unequivocally enforce and comply with EU Treaty constitutive values, EU law and Better Regulation commitments in migration policies.This Book falls within the scope of the I-CLAIM Horizon Project.